2002
DOI: 10.1002/tera.10060
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of spina bifida and anencephaly during the transition to mandatory folic acid fortification in the United States

Abstract: The decline in the prevalence of spina bifida was temporally associated with folic acid fortification of US grain supplies. The temporal association between fortification and the prevalence of anencephaly is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 284 publications
(130 citation statements)
references
References 12 publications
3
123
1
3
Order By: Relevance
“…It is well established that folic acid taken prior to conception and early in gestation reduces a woman's risk of having a baby with a neural tube defect (NTD) [19][20][21][22][23] and possibly other defects [24,25], and recent studies suggest that maternal folate status has a direct effect on low birth weight and preterm delivery [26,27]. Smoking during pregnancy is an independent risk factor for preterm birth and for certain types of birth defects including orofacial clefts and clubfoot [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that folic acid taken prior to conception and early in gestation reduces a woman's risk of having a baby with a neural tube defect (NTD) [19][20][21][22][23] and possibly other defects [24,25], and recent studies suggest that maternal folate status has a direct effect on low birth weight and preterm delivery [26,27]. Smoking during pregnancy is an independent risk factor for preterm birth and for certain types of birth defects including orofacial clefts and clubfoot [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Stratified analysis was used to assess factors potentially modifying the association between preterm birth and birth defects. Factors assessed included: maternal race/ethnicity (non-Hispanic white, non-Hispanic black, Hispanic, other), maternal age in years (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), C35) number of previous live births (none, 1 or more), maternal education (\12 years, 12 years, [12 years), initiation of prenatal care (first trimester, second trimester, third trimester, no prenatal care), and delivery method (vaginal, vaginal birth after C-section, primary C-section, repeat C-section). To improve comparability, birth certificates were used as the source of these data for both the numerator and denominator.…”
Section: Methodsmentioning
confidence: 99%
“…The level of fortification differs among countries; however, in all cases, these programs are designed to reduce the prevalence of pregnancies with NTDs. In the USA and Canada, these folic supplementation programs were thought to be successful because the population folate status was improved (Ray et al 2002) and reduced rates of NTDs were noted (Honein et al 2001; Williams et al 2002), although the results varied depending on ethnicity (Williams et al 2005). Data from the USA reported from the NHANES trial (Pfeiffer et al 2012) showed that the mean concentration of serum and RBC folate increased dramatically from the prefortification period (1988–1994) to the postfortification period (1990–2010), from 16.7 ± 0.5 to 41.0 ± 0.3 nM and from 747 ± 10 to 1120 ± 7 nM, respectively, resulting in a 31% reduction in the occurrence of NTDs (Williams et al 2002).…”
Section: Response Of Folate Status To Folate Intake and Supplementationmentioning
confidence: 99%
“…Implementation of food fortification with folic acid in 1998 in USA and Canada caused a significant decrease of NTDs. The incidence of spina bifida decreased by 31% and 53% in the USA and Canada, respectively [27,28]. A study conducted by Ionescu-Ittu et al showed a significant drop in incidence of congenital heart defects in Quebec province in Canada after implementation of mandatory food fortification [29].…”
Section: Discussionmentioning
confidence: 99%